Suspended and Dissolved Sediment Concentrations of Two Disturbed Lowland Forested Watersheds in Air Hitam Forest Reserve, Selangor - Lai, Food See; Musa, Samsuddin (1985)
Observations on suspended and dissolved sediment concentrations were made from two disturbed watersheds situated in Air Hitam Forest Reserve, Selangor over a period of six months. Samples were taken during low flows and high flows. Results obtained showed that the difference in suspended sediment concentrations from the watersheds is significant. Suspended sediment concentrations ranged from 2 -1305 mg/l for watershed A, a relatively more disturbed watershed and 1 - 292 mg/l for watershed B, a less disturbed catchment. For dissolved sediment concentration, the range was 4 -136 mg/l for watershed A ·and 3 - 90 mg/l for watershed B, of which the difference is not statistically significant. The Findings in this study demonstrate rather clearly the effect of logging on sediment concentrations and variance over time in the two watersheds with logging operations ceasing about a year apart.